An Immunosensor for Pathogenic Staphylococcus aureus Based on Antibody Modified Aminophenyl-Au Electrode. (10th November 2013) - Chrouda, Amani; Braiek, Mohamed; Rokbani, Karima Bekir; Bakhrouf, Amina; Maaref, Abderrazak; Jaffrezic-Renault, Nicole
Abstract : The objective of this work is to elaborate an immunosensing system which will detect and quantify Staphylococcus aureus bacteria. A gold electrode was modified by electrografting of 4-nitrophenyl diazonium, in situ synthesized in acidic aqueous solution. The immunosensor was fabricated by immobilizing affinity-purified polyclonal anti S. aureus antibodies on the modified gold electrode. Cyclic voltammetry (CV) and Faradaic Electrochemical Impedance Spectroscopy (EIS) were employed to characterize the stepwise assembly of the immunosensor. The performance of the developed immunosensor was evaluated by monitoring the electron-transfer resistance detected using Faradaic EIS. The experimental results indicated a linear relationship between the relative variation of the electron transfer resistance and the logarithmic value of S. aureus concentration, with a slope of 0.40 ± 0.08 per decade of concentration. A low quantification limit of 10 ± 2 CFU per ml and a linear range up to 10 7 ± 2 × 10 6 CFU per mL were obtained. The developed immunosensors showed high selectivity to Escherichia coli and Staphylococcus saprophyticus .